From Khas Root to Rooh khas - Singh, Bharat; Sankhala, Kailash Singh (Indian Forester, 1957)
The distribution of khas grass ( Vetiveria zizanioides Nash) in Bharatpur District of Rajasthan, the botanical characteristics and the indigenous method of distillation of khas root for essential oil described.